Integrating environmental considerations in the agricultural policy process: Evidence from Nigeria - Babu, Suresh Chandra; Mavrotas, George; Prasai, Nilam (Elsevier, 2018)
Policy processes that design, develop, and implement sectoral policies often leave environmental considerations to a central environmental authority. As a result, the environmental implications and consequences of policies and programs, even when they are explicitly recognized as a part of their mandate, are often ignored at the time of implementation. In this paper, we show how the role of individual, organizational, and system level factors in enhancing the ability of policy actors is crucial in better integration of environmental considerations in policy processes. Using data collected in Nigeria, we develop empirical evidence on such factors so that the sectoral policy process can be improved for environmental outcomes. The results indicate that explicit identification of environmental challenges, better collaboration and communication between research and policymaking, and a combination of the expertise of young analysts with the experience of senior policymakers can improve explicit consideration and follow-up of environmental issues in sectoral policy process. The lessons from this paper are also applicable to the environmental considerations of the current policy roadmap for the promotion of the agricultural sector in Nigeria, the Agriculture Promotion Policy (APP), and to other developing countries attempting implementation of such sectoral policies.